Chowing down - Holt, Jeff (New Haven register (New Haven, Conn. : 1961), 2007)
The Solo-Preneur Council of the Greater New Haven Chamber of Commerce meets at 8 a.m. at the chamber, 900 Chapel St. The subject will be MasterMind Groups, created by famed motivational author Napoleon Hill. Call 782-4342. A--The College of Business at the University of New Haven will hold a free public forum on "Interfirm Collaboration, Cross-border Knowledge Transfer, and Firm Performance: An Empirical Study," at 12:30 p.m. at Maxcy Hall, room 124. The seminar will feature the work of Subroto Roy, associate professor in the Department of Marketing and Communication. Call A. E. Rodriguez at 932-7372 or e-mail arodriguez@newhaven.edu. The Rotary Club of Branford meets at 12:15 p.m. at the Italian American Social Club, 40 Hamre Lane. Board member Alpha Coiro will offer a slide presentation on "Cambodia: Land of Angkor and Anguish." Call 488-7103. A--The New Haven Public Library, 133 Elm St., will hold a free four-hour seminar on "Re-Imagining Fund-Raising" at 10 a.m. The speaker will be Jane Lennox of Lennox Associates and The Nonprofit Consulting Group. Registration is required by calling 946-8835 or visiting www.guidezilla.com/nhfpl.